ANALISIS KOHESI LEKSIKAL PADA PODCAST â€œIF YOU KEEP YOUR MOUTH SHUT, YOUâ€™LL BE SURPRISED WHAT YOU CAN LEARNâ€ OLEH S. TOWN - Ayurangga, Egi Ayis; Pelealu, Hetty; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Â This research entitled An Analysis Lexical Cohesion in Podcast â€œIf You Keep Your Mouth Shut, Youâ€™ll Be Surprised What You Can Learnâ€ Podcast By S.Town is the requirement to accomplish the Bachelor Degree at Faculty of Humanities, Sam Ratulangi University. The objectives of this research are to identify,clasify and analyze descriptively the aspects of lexical cohesion on the Podcast S.Town. The theory used in this research is from Halliday and Hasan (1976). The theory focused on the aspects of lexical cohesion. The lexical cohesion consisted of reiteration (repetition, synonym, antonym, hyponym, meronymy) and collocation. The Podcast is taken from one of podcast episode in www.Stownpodcast.com. The result of this research shows that there are 53 lexical cohesion items consisting of 47 reiteration (15 repetition, 8 synonimy, 8 antonimy, 11 meronimy, and 5 hyponimy) and 6 colocation items.Keyword: Cohesion, Lexical, Podcast